Carbon and Nutrient Cycling in Two Central Himalayan Sal (Shorea robusta Gaertn.) Forests - Rana, B. S.; Khanna, R. K.; Verma, S. K. (Indian Forester, 2010)
Carbon and nutrient budgets for two Central Himalayan Sal (Shorea robusta Gaertn.) forests (Sal old growth and new growth forests) are described. The total Carbon storage in Sal old growth forest (379 t Cha-1) was greater than Sal new growth forest (242 t Cha-1). However, net primary productivity values (9.3-10.11C ha-1yr-1) revealed almost similar potential of both forests. Of the total carbon uptake in ecosystem, the net accumulation accounted for 33%. Of the total nutrient storage in two forests, vegetation pool accounted for 53-54% N; 67.72%, P; 90-93% K; 18034% Ca; and 77-78% Na. The net primary productivity and nutrient uptake in Sal new growth forest were higher than that of old growth forest, irrespective of nutrient storage in biomass. The total nutrient uptake (kg ha-1 yr-1) by the vegetation was: 155-178N; 13-15P; 73-85K; 119-135 Ca; and 7-8 Na in two forests. Under relatively undisturbed condition, Central Himalayan Sal forests are efficient carbon sink and nutrient rich ecosystems.